DNA-AuNP networks on cell membranes as a protective barrier to inhibit viral attachment, entry and budding. (January 2016) - Li, Chun Mei; Zheng, Lin Ling; Yang, Xiao Xi; Wan, Xiao Yan; Wu, Wen Bi; Zhen, Shu Jun; Li, Yuan Fang; Luo, Ling Fei; Huang, Cheng Zhi
Abstract: Viral infections have caused numerous diseases and deaths worldwide. Due to the emergence of new viruses and frequent virus variation, conventional antiviral strategies that directly target viral or cellular proteins are limited because of the specificity, drug resistance and rapid clearance from the human body. Therefore, developing safe and potent antiviral agents with activity against viral infection at multiple points in the viral life cycle remains a major challenge. In this report, we propose a new modality to inhibit viral infection by fabricating DNA conjugated gold nanoparticle (DNA-AuNP) networks on cell membranes as a protective barrier. The DNA-AuNPs networks were found, via a plaque formation assay and viral titers, to have potent antiviral ability and protect host cells from human respiratory syncytial virus (RSV). Confocal immunofluorescence image analysis showed 80 ± 3.8% of viral attachment, 91.1 ± 0.9% of viral entry and 87.9 ± 2.8% of viral budding were inhibited by the DNA-AuNP networks, which were further confirmed by real-time fluorescence imaging of the RSV infection process. The antiviral activity of the networks may be attributed to steric effects, the disruption of membrane glycoproteins and limited fusion of cell membrane bilayers, all of which play important roles in viral infection. Therefore, our results suggest that the DNA-AuNP networks have not only prophylactic effects to inhibit virus attachment and entry, but also therapeutic effects to inhibit viral budding and cell-to-cell spread. More importantly, this proof-of-principle study provides a pathway for the development of a universal, broad-spectrum antiviral therapy.